Analysis and design of simply supported plate girder to British Standard 5950 and Eurocode 3 [electronic resource] - Pon, Chew Leng, 1987-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2011